2004
DOI: 10.1103/physrevb.70.094402
|View full text |Cite
|
Sign up to set email alerts
|

Site-dilution in the quasi-one-dimensional antiferromagnetSr2(Cu1xPdx

Abstract: We investigate the Néel temperature of Sr 2 CuO 3 as a function of the site dilution at the Cu ͑S =1/2͒ sites with Pd ͑S =0͒, utilizing the muon spin relaxation ͑SR͒ technique. The Néel temperature, which is T N = 5.4 K for the undoped system, becomes significantly reduced for less than one percent of doping Pd, giving a support for the previous proposal for the good one-dimensionality. The Pd concentration dependence of the Néel temperature is compared with a recent theoretical study [S. Eggert, I. Affleck, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 31 publications
0
49
1
Order By: Relevance
“…28 The value of x Curie is found to be about a half of the Pd concentration, x. This is reasonably explained as follows.…”
Section: Magnetic Susceptibilitymentioning
confidence: 48%
See 1 more Smart Citation
“…28 The value of x Curie is found to be about a half of the Pd concentration, x. This is reasonably explained as follows.…”
Section: Magnetic Susceptibilitymentioning
confidence: 48%
“…These behaviors of χ are similar to those reported in the literature. 17,18,28 The experimental data of χ are well fitted using the following equation as in the former report: 18…”
mentioning
confidence: 99%
“…This study is a continuation of our earlier work in which we studied the crystals of the layer perovskite type [3]. In recent years the mixed Sr 2 Pd 1−x Cu x O 3 and Sr 2 Cu 1−x Ni x O 3 phases, being structural analogues of Sr 2 CuO 3 , have been studied by different methods [4][5][6][7]. Direct information about delocalization of the Cu 2+ unpaired electron on the nearest cations can be obtained from electron paramagnetic resonance spectra.…”
Section: Introductionmentioning
confidence: 93%
“…24,25 One problem is that Zn 2+ , a traditional S = 0 substitute for Cu 2+ , does not readily enter the crystal structure during synthesis. 25 To date, only one focused study of long-range ordering in site-diluted Sr 2 CuO 3 has been reported. It was based on Pd 2+ substitution, but the exact concentration of defects was shown to be difficult to control, and no systematic studies for the concentration dependence of T N was performed.…”
mentioning
confidence: 99%